Mediating Effect of Customer Satisfaction on Relationship Marketing and Customer Loyalty among Commercial Banks Customers in Awka, Anambra State - U. Omeje and Moses C. Olise, Nkemjika (British Journal of Marketing Studies, 2022)
The banking industry is one of the largest sectors dealing with individual customers directly. The success and profitability of a company is based on the number of customer base and their ability to maintain good relationship with their customers and satisfy them efficiently. Therefore, this study seeks to examine the mediating effect of customer satisfaction on relationship marketing and customer loyalty among commercial bank customers in Awka, Anambra state. Specifically, the study examined the effects of relationship marketing concepts (trust, commitment, communication and conflict handling on customer loyalty. Data was collected from 691 respondents and the hypotheses tested using macro process via SPSS version 17. The result showed that relationship marketing dimensions used in this study (trust, commitment, communication and conflict handling) has significant influence on customer loyalty. Furthermore, customers’ satisfaction has significant mediating influence on the relationship between the components of relationship marketing (trust, commitment, communication and conflict handling) and customer loyalty. It was therefore recommended that since customer satisfaction is a determinant of customer loyalty, via relationship marketing activities there is need for banks to satisfy their customers so as to encourage them to remain loyal to the bank through continuous patronage.